2015
DOI: 10.1186/s40164-015-0028-8
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer brain metastases: the last frontier

Abstract: Breast cancer is a common cause of brain metastases, with metastases occurring in at least 10–16 % of patients. Longer survival of patients with metastatic breast cancer and the use of better imaging techniques are associated with an increased incidence of brain metastases. Unfortunately, patients who develop brain metastases tend to have poor prognosis with short overall survival. In addition, brain metastases are a major cause of morbidity, associated with progressive neurologic deficits that result in a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(124 citation statements)
references
References 99 publications
(101 reference statements)
3
117
0
4
Order By: Relevance
“…32 For this reason, it has been suggested that breast cancer tumor cells need some time to develop their ability to penetrate through the BBB and colonize the brain. 33 In this frame, it would be interesting to investigate and compare the ability of metastatic breast cancer cells to interact with the endothelium from different organs (adhesion, transmigration processes).…”
Section: Discussionmentioning
confidence: 99%
“…32 For this reason, it has been suggested that breast cancer tumor cells need some time to develop their ability to penetrate through the BBB and colonize the brain. 33 In this frame, it would be interesting to investigate and compare the ability of metastatic breast cancer cells to interact with the endothelium from different organs (adhesion, transmigration processes).…”
Section: Discussionmentioning
confidence: 99%
“…There is a huge number of molecular and genetics biomarkers other than ER, PR and HER2 receptors that were extensively studied in association with BM development in patients with early diagnosed as well as metastatic BC [26][27][28][29]. The substantial progress in cancer multi-omics disciplines (such as genomics, proteomics and transcriptomics) in recent years allowed the examination of distinct molecular patterns of BC tumours predicting the higher probability of development of BM after the disease recurrence.…”
Section: Molecular and Genetic Biomarkers Other Than Hormone And Her2mentioning
confidence: 99%
“…However, management of metastatic disease in the brain and/or central nervous system (CNS), observed in up to 50% of HER2 þ breast cancer patients, continues to be a clinical challenge in large part due to the inability of mAbs to sufficiently cross the blood-brain barrier. Although small-molecule inhibitors of HER2 exist and have been clinically approved, their single-agent efficacy in the context of metastatic disease to the brain has been limited (4,5). While HER2-targeted therapy in combination with conventional agents has shown some promise for the treatment of patients with metastatic breast cancer, control of brain metastases remains a significant unmet clinical need, as most patients survive less than 2 years following CNS involvement.…”
Section: Introductionmentioning
confidence: 99%